PENGARUH PROPORSI KOMISARIS INDEPENDEN DAN KEBERADAAN KOMITE AUDIT TERHADAP TAX AVOIDANCE: STUDI PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Pradasari, Puput; Ermawati, Nanik (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2018)
The purpose of this research is to examine the influence of proportion of independent directors and the existence of an audit committee against tax avoidance. The population in this study is an industrial companies and real estate properties listed on the Indonesia Stock Exchange period of 2012-2016. The sample selection is conducted by using purposive sampling method, therefore as many as 173 of observation sample was obtained. Analysis technique to examine the hypotheses is multiple linier regressions. The result of this research shows proportion of independent directors have no significant on tax avoidance. The existence of an audit committee has positive significant influence on tax avoidance